Cryptography with fast point multiplication by using ASCII codes and its implementation. (1st January 2013) - Shankar, T.N.; Sahoo, G.; Niranjan, S.
This paper describes the point multiplication through addition-subtraction method and its implementation through MATLAB to speed up the operations in elliptic curve cryptography (ECC) with ASCII codes under limited hardware resources. To further decrease the computation time, we employed the non-adjacent form of a binary sequence to decrease the total number of additions in ECC encryption/decryption. This paper implements ASCII code table for convenient manipulation of characters, and addition-subtraction method for point multiplication with less time and space complexity with its implementation in MATLAB. We can fully use the idle time of hardware resources by relaxing the data dependency on those arithmetic operations performed to accomplish the point multiplication. As a result, hardware utilisation increases. ECC is the most applicable and suitable algorithm for mobile devices due to its compact shape and size.